Utilização de maiores percentuais de pellet feed na etapa de aglomeração a frio da sinterização de minério de ferro a partir da adição de aglomerantes - Fabiano Maia Linhares (2019)
The sintering process is the main producer of agglomerated iron burden for the blast furnace. The world tendency on the reduction of high quality iron ore availability, leading to an increase of ultra-fines production, and the necessity of improving the productivity of this process made the cold agglomeration the focus of research and efforts. Many studies were made seeking the production of mixtures with bigger mean particle size but the partial substitution of sinter feed by pellet feed have some limitations and produces direct impact on the bed permeability. The usage of organic binders, although already being used and studied in the pelletizing process, is still not a practice in the sintering process. This work has as main objective the study of the possibility of the use of organic binders in the sintering mixture in order to allow the increase in the pellet feed participation without producing deleterious effects on the process and the final product, ensuring high productivity and good physical and metallurgical quality of the produced sinter. Laboratory scale cold agglomeration experiments were made with three binders: Alcotac CS, Peridur and a Brazilian mineral coal. The experiments showed that only the cellulose derivate binder was capable of producing agglomerates with equal or greater mean particle size when compared with the base test, used as reference, for practically all performed tests, regarding the values of d50 and Sauter mean diameter, besides promoting the increase on the adhering layer thickness and stability of the nucleiadhering layer interface of the micro pellets. The addition of pellet feed in the mixture, without the presence of binders, led to a decrease in the particle mean size of the agglomerate produced.